(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Laser treatment is generally used for tissue restoration. Restorative soft tissues include objective, practicaland difficult responses.The goal of the research have being to estimate the irradiation capabilities the helium neon laser irradiationon three different types of wounds depth.Sixty young male rats were used in this study, divided into three groups. (20 per group) Wounds were createdwith different depth for the first, second and third group have been irradiated by the laser using He-Neenergies flowing 4 minutes, five out of twenty animals left without radiation is considered to control.Biopsy was taken from all rats for histological examination at 1, 3 and 7 days after surgery. The resultsshowed a clear enhancement of treatment wounds from control, Helium neon laser failure in the treatmentof very deep wounds.